A Pattern-Growth Sentence Compression Technique For Malay Text Summarizer - Alias, Suraya (2018)
Automatic Text Summarization (ATS) has benefited users in terms of identifying and extracting the most salient information from a given text with less effort. The application of Sentence Compression (SC) in ATS is to remove unimportant constituents from a summary sentence while preserving the salient ones by keeping the sentence’s grammar intact. Most previous SC techniques have a high dependency on syntactic rules and knowledge applied to individual word or phrase to cater the removal decision. Despite the ability to produce a new grammatical compressed sentence, prior approaches still suffer several drawbacks including the failure to include some significant and relevant sentences in constructing the final summary sentence.